P33 Patients with pulmonary arteriovenous malformations and hereditary haemorrhagic telangiectasia report forced expiratory manoeuvres during pulmonary function tests provoke nosebleeds and migraines. (15th November 2016) - Tighe, HC; McKernan, H; Springett, JT; Babawale, L; Perks, J; Patel, T; Shovlin, CL
Abstract : Introduction and objectives: Forced expiratory manoeuvres during lung function testing produce major pressure swings that are often overlooked by referring clinicians. Standard tests use a noseclip to prevent air leakage through the nose. Our goal was to examine how often the tests caused clinical sequelae such as nosebleeds in people with abnormal nasal and pulmonary vasculature due to hereditary haemorrhagic telangiectasia (HHT). Methods: With ethical approval, self-reported migraine features and exacerbations were examined in HHT subjects with and without pulmonary AVMs, for a series of noninvasive and invasive investigations, using an unbiased online survey. Results: Of 677 HHT-affected participants, 284 reported performing forced expiratory manoeuvres either with or without a noseclip in place. The median age was 54 years (interqurtile range 44–62) and the majority were female. All described nosebleeds: 130 (46%) experienced these at least daily, and a further 95 (33%) at least once per week. Only 1 of 253 (0.4%) reported nosebleeds were worse after finger oximetry measurements, compared to 53/282 (18.8%) after "blowing out hard without a noseclip" (chi-squared p < 0.0001). A higher proportion still reported nosebleeds were worse when a noseclip was used (66/192 (34.3%, p = 0.0003)). Similarly, migraine headaches (which are more frequent in people with HHT), were reported to be worse after forced expiratory manoeuvres both with (10/85 (11.7%) and without (11/105 (10.5%)) a noseclip, but not after oximetry or being weighed. Conclusion: Noseclip use should be restricted in people already experiencing regular nosebleeds, and further pretest information may be required.